(untitled) (Research, Society and Development, 2024)
This literature review aims to discuss the relevance and benefits of using CO2 laser in the treatment of postmenopausal genitourinary syndrome (GSM). This syndrome is characterized by a set of signs and symptoms, such as vaginal dryness, dyspareunia, atrophy and reduced elasticity of vaginal tissues, caused by the reduction in estrogen levels after menopause. In this sense, given the need for non-hormonal therapeutic alternatives and the search for safe and effective treatments for GSM, the fractional CO2 laser appears as an innovative and promising approach. This approach, according to recent studies, has been shown to be an effective therapeutic option in treating the syndrome, despite still being a method little used due to the high cost of the instruments required for this procedure.